A radio halo surrounding the Brightest Cluster Galaxy in RXCJ0232.2–4420: a mini-halo in transition?. (11th May 2019) - Kale, Ruta; Shende, Krishna M; Parekh, Viral
ABSTRACT: Diffuse radio sources associated with the intra-cluster medium are direct probes of the cosmic ray electrons and magnetic fields. We report the discovery of a diffuse radio source in the galaxy cluster RXCJ0232.2–4420 (SPT-CL J0232–4421, z = 0.2836) using 606 MHz observations with the Giant Metrewave Radio Telescope. The diffuse radio source surrounds the Brightest Cluster Galaxy in the cluster-like typical radio mini-haloes. However the total extent of it is 550 × 800 kpc 2, which is larger than mini-haloes and similar to that of radio haloes. The BCG itself is also a radio source with a marginally resolved core at 7 arcsec (30 kpc) resolution. We measure the 606 MHz flux density of the RH to be 52 ± 5 mJy. Assuming a spectral index of 1.3, the 1.4 GHz radio power is 4.5 × 10 24 W Hz −1 . The dynamical state of the cluster has been inferred to be 'relaxed' and also as 'complex', depending on the classification methods based on the morphology of the X-ray surface brightness. This system thus seems to be in the transition phase from a mini-halo to a radio halo.